Are there differences in immune responses following delivery of vaccines through acutely or chronically sun‐exposed compared with sun‐unexposed skin?. Issue 2 (6th November 2019) - Hart, Prue H.; Norval, Mary
Summary: The majority of human vaccines are administered above the deltoid muscle of the arm, a site that is chronically sun‐exposed in many people. It is known that exposure of the skin to the UV wavelengths in sunlight stimulates systemic immunosuppression, an outcome that is associated with reduced immunity to microbial infections in animal models. Here we consider whether immunization of humans through a UV‐irradiated skin site will lead to a less effective immune response compared with immunization through an unexposed site. Studies showing that the efficacy of vaccination can be reduced when surrogates of increased levels of sun exposure, such as latitude of residence and season of the year, are considered. Results from a limited number of intervention experiments in humans demonstrate a similar pattern. To provide an explanation for these findings, changes in the number and functional potential of immune cells in chronically sun‐exposed compared with unexposed skin are outlined. UV radiation‐induced changes to skin cells are also relevant when considering skin sites for administration of immune‐tolerizing peptides. The review provides the basis for further research into the effects of acute and chronic UV radiation exposure on skin cells in the context of vaccination. Abstract : The review covers the effects of acute and chronic UV radiation exposure on skin cells in the context of vaccination for immunity or tolerance. Will immunization of humans through a UV‐irradiated skin site (for example above the deltoid muscle of the arm) lead to a less effective immune response compared with immunization through an unexposed site?